Improving the oxidative stability of fats in burgers - Veta Adrijan, Pejkovski Zlatko, Belichovska Katerina, Belichovska Daniela (Faculty of Agricultural Sciences and Food, University Ss. Cyril and Methodius in Skopje, 2016)
The effects of using a sage (Salvia officinalis) both in its dry form and as an extract have been examined, as well as the spice mixture of oregano (Оriganum viridis) and winter savory (Satureja Montana) on the oxidative stability of fats, sensory characteristics, pH-values, weight loss during grilling and microbiological profile of burgers. Burgers, produced according to the common technological procedure, have been used in examinations. Five groups of products have been made: R- referent products without additives; R/B+A products with additives, R/S products with Salvia officinalis added in its dried form (0.2 %); R/Se products with 0.05% of Salvia officinalis extract added; R/O products with commercial spice mixture - oregano plus added (0.2%). Following examinations have been done: pH-value measurement (at 3 and 7 days after production), grilling weight loss (at 3 and 7 days after production), sensory characteristics (at 3 and 7 days after production), microbiological analysis of burgers (at 1 and 7 days after production) and determination the level of fats oxidation – TBARS test at 7 days after production (the products have been kept at a temperature of 0-4o C), and 90 days after production (the products have been kept at a temperature of -18o C). The lowest pH-value (5.83), at 7 days after production has been determined in group R\Se, while the highest pH-value (5.97) has been determined in group R\B+A, which indicates shorter shelf life of the product. The R/Se products have the highest (14,25%) grilling weight loss. The lowest pH-value, 7 days after production, has been measured in this group which coincides with the statement that as the pH-value decreases, the grilling weight loss increases. At 7 days after production, the R/Se products are claimed to be more sensory acceptable than the rest of the groups of products and they have been the highest evaluated by taste panelists. The R/O group of products has been given the best results in microbiological analysis, which confirms the antimicrobial activity of the spice products. This group has the lowest level of fats oxidation, or the lowest content of malonaldehyde (only 0.567 mg/kg).
Keywords: oxidative stability of fats, sage, oregano, burgers